The resistance of black currant varieties against the dark kovalyk in the Forest conditions of Ukraine - Bakalova, A.; Gritsyuk, N.; Stolyar, S.; Ivachenko, I. (Scientific Progress & Innovations, 2024)
In recent years, the dark weevil in the conditions of the Polissia of Ukraine has acquired a large scale in currant agrocenoses, and now it is an actual topic, which is presented in the article of a scientific work. The study of the resistance of different varieties of blackcurrants to black currant makes it possible to draw an excellent conclusion that the use of resistant varieties in the cultivation of blackcurrants, first of all, makes it possible to reduce the population of the true wireworm by 2‒4 times, and the quality of black currant bunches increases. Resistant varieties have well-developed roots with a fibrous structure. In unstable varieties, the root system when damaged by the larvae is weak, drooping, small roots damaged by the dark weevil dry out, darken and rot. Over the years of the work, various age stages of the larvae of the "real wireworm" were observed. A four-year-old larva stops feeding in the second year of life and pupates. The metamorphosis of the black currant takes place on a varietal collection of black currants in different decades of the month of May. The phenological calendar developed by us during the research proves that the phytophagus in the conditions of the Zhytomyr region gives only one generation in 2 years. That is, the developed phenological system of the phytophagous development, which is combined with the phenological development of black currant, makes it possible to clearly estimate the predicted productivity and biological development of black currant. According to the assessment of economic efficiency, the yield is from 4.5 to 6.4 t/ha. According to these indicators, the most resistant varieties of blackcurrant were found in terms of the population of black currant and productivity, where resistant varieties were found, Lydia, Karpaty, Black Pearl from 5.8 to 6.4 t/ha, profit 53938 to 61138 UAH/ha, profitability up to 390 %.